Fidelização de doadores de sangue voluntários e habituais: uma prática de educação em saúde - Capra, Micheli Serpa (Universidade do Vale do Rio dos Sinos, 2013)
This study started from the premise of knowing the characteristics and motivations of repeat blood donors of the Hematology Service of the Santa Casa de Porto Alegre-RS. Aiming to create strategies for service improvement and retention of blood donors as well as the ability to transform eventual blood donors into loyal donors. To meet the objectives of the study it was decided for the use of mixed methodology, quantitative and qualitative approach, seeking to identify beyond the data concerning blood donor loyalty as well as the aspects related to their intention to make the donation. It was observed that feelings of solidarity, altruism and love for others are the motivators of this group that donates blood regularly (loyal donors). The quality of care is considered one of the questions of most impact on blood donation loyalty process and determinant for the substantiation of the adherence to this behavior. The screening interviews conducted by nurses and that precedes the blood collection may be one of the deciding factors not only referring to the place where the blood donations will be carry out, as adherence to become donor. The clinical trial, so in addition to a key moment for the secure blood donation, provides professionals with a time for health promotion. The health professional should make use of every opportunity to educate citizens for a healthy life. Contact with candidates for blood donation, patients and their families should be seen as an opportunity for education and good health practices. Technical knowledge should be aligned to individual needs in order to conduct the explanations, guidelines and answer the questions effectively seeing at this time the possibility of transformation and change generation. For this the effective training of health teams is necessary, so that they become active in such a motivated way and aware of the cause for which they are working. There is a need for improvement and humanization of the donor related care and treatment processes to reduce barriers to blood donation contributing to the retention of donors.
Keywords: Educação em saúde; Doador de sangue; Altruísmo; Health Education; Blood donor; Altruism; ACCNPQ::Ciências da Saúde::Enfermagem